Associations of history of traumatic brain injury with markers of brain health among older men in the Vietnam Era Twin Study of Aging - Alexander Ivan B. Posis; Jeremy A. Elman; John E. Alcaraz; Humberto Parada, Jr.; Aladdin H. Shadyab; Christine Fennema-Notestine; Donald J. Hagler, Jr.; Michael J. Lyons; Matthew S. Panizzon; Chandra A. Reynolds; Carol E. Franz; William S. Kremen; et al. (NeuroImage: Clinical)
Background: Traumatic brain injury (TBI) is associated with increased risk of dementia, but it is unclear how earlier life TBI is related to brain health in older age. Methods: This cross-sectional study compared 517 male Vietnam Era Twin Study of Aging participants with and without a history of TBI (34 % with TBI; median age = 68 [range = 61–72] years). Validated brain age models were used to calculate predicted brain age difference (PBAD and Brain-PAD) scores. A multichannel segmentation approach was used to quantify abnormal white matter signal intensities (AWM). Restriction spectrum imaging (RSI) was used to model multishell diffusion in restricted (intracellular) and free water compartments. Multivariable linear mixed-effects models estimated associations of TBI with PBAD, Brain-PAD, AWM, and RSI outcomes. We assessed moderation in associations of TBI with PBAD, Brain-PAD, AWM, and RSI outcomes by apolipoprotein E epsilon 4 (APOE-ε4) status, depressive and posttraumatic stress symptom severity, and loneliness. Results: PBAD, Brain-PAD, AWM, and global white matter RSI measures did not differ by TBI status but those with history of TBI showed lower restricted diffusion in the inferior longitudinal fasciculus bilaterally and the left inferior occipital fasciculus compared to those without TBI, after adjusting for age and scanner (p-values < 0.05). Results did not differ by APOE-ε4 status, psychiatric symptoms, or loneliness for any primary outcome. Conclusions: There may be subtle white matter microstructural changes after a TBI event that persist even after over four decades after initial injury. Further research is needed to determine if these differences relate to increased TBI-associated risk of dementia.